The Sistine Chapel paradise in Rome - Pfisterer, Ulrich 1968- (Getty Research Institute, 2018)
"The Sistine Chapel: Paradise in Rome is a scholarly yet accessible history of the Sistine Chapel. Through a study of the main campaigns to adorn the chapel, Ulrich Pfisterer argues that art transformed the chapel into a pathway to the kingdom of God, legitimizing the absolute authority of the popes"...Provided by publisher